2019
DOI: 10.1016/j.apergo.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Measuring mental workload using physiological measures: A systematic review

Abstract: Technological advances have led to physiological measurement being increasingly used to measure, and predict operator states. Mental workload (MWL) in particular has been characterised using a variety of physiological sensor data. This state of the art review contributes a synthesis of the literature. We present a systematic review of 58 peer reviewed journal articles which present original data using primarily peripheral nervous system (PNS) measures to include electrocardiographic, blood pressure, respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
250
2
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(268 citation statements)
references
References 89 publications
11
250
2
5
Order By: Relevance
“…Studies have suggested that a 4-item NASA-TLX may be more suitable for measuring nurse workload, however there is still controversy regarding the application of 4-item or 6-item versions of NASA-TLX in the clinical setting (Galy et al, 2018;Charles et al, 2019). Our current study utilized the 6-item version of NASA-TLX in order to assess different aspects of nurse workload.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that a 4-item NASA-TLX may be more suitable for measuring nurse workload, however there is still controversy regarding the application of 4-item or 6-item versions of NASA-TLX in the clinical setting (Galy et al, 2018;Charles et al, 2019). Our current study utilized the 6-item version of NASA-TLX in order to assess different aspects of nurse workload.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used instrument for assessment of overall subjective workload is the National Aeronautics and Space Administration Task Load Index (NASA-TLX), which contains a total of six dimensions: mental, physical, and temporal task demands, as well as effort, frustration, and perceived performance (Charles et al, 2019). The NASA-TLX has been validated and widely used as an assessment tool in a healthcare setting.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of the physiological response and inferring cognitive states, with and without system adaptation has been demonstrated in previous studies [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. However, there are still considerable challenges with the implementation of such methods, where some extensive reviews have identified that measures of MWL are not universally valid for all task scenarios [ 19 , 20 ]. A reason for this is that the physiological responses for MWL can be scenario dependent and are thus influenced by a range of individual differences and task characteristics [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Measurements usually fall into three broad categories. Behavioral measurements such as various types of eye movement (de Greef et al, 2009) or gross motor behaviors (Boxtel and Jesserun, 1993), subjective measures including self-reporting scales such as the multidimensional SWAT (Reid and Nygren, 1988) and NASA Task Load Index questionnaires (Hart and Staveland, 1988), and objective physiological measurements which capture a signal that potentially scales or correlates with task loading (Chen et al, 2012;Lean and Shan, 2012;Young et al, 2015;Charles and Nixon, 2019). Among the last are measures such as electroencephalography (EEG), electromyography (EMG), electrocardiography (ECG), galvanic skin response (GSR), inertial measurements, and speech (Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of physiological measurements lies in their objectivity and, in recent years, in the low-cost and ease of deployment of body-worn sensors. Many studies have measured task loading using a limited number of physiological signals such as eye movement, or EEG, or GSR in an attempt to measure task loading along one or few dimensions (Smallwood and Schooler, 2006;Feng et al, 2013;Lean and Shan, 2012;Charles and Nixon, 2019). However, few studies have combined modalities so that estimation error can be reduced while classification accuracy can be increased (Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%